2014
DOI: 10.1179/2047773214y.0000000128
|View full text |Cite
|
Sign up to set email alerts
|

Performance of three rapid screening methods in the detection ofSchistosoma haematobiuminfection in school-age children in Southeastern Nigeria

Abstract: Background: A cross-sectional study of primary school children was conducted to evaluate and compare the performance of some rapid screening methods in the detection of Schistosoma haematobium infection in Nigeria Cement Factory (NigerCem) and Nike Lake areas of Southeastern Nigeria. Methods: Urine samples of school children were examined for macro-haematuria and tested for microhaematuria and proteinuria using reagent strips followed by egg microscopy. Self-reported haematuria was assessed using simple questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…This finding is similar to those of previous studies in low transmission settings (Lwambo et al, 1997a;Robinson et al, 2009). However, the high PPV of urine reagent strips in Uwandani Shehia area is similar to other moderate transmission areas in SSA (Bocanegra et al, 2015;Okeke and Ubachukwu, 2014;Robinson et al, 2009). Hence, these variations in performance of the urine reagent strips in low transmission settings will require confirmation of positive results with more sensitive diagnostic tests.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is similar to those of previous studies in low transmission settings (Lwambo et al, 1997a;Robinson et al, 2009). However, the high PPV of urine reagent strips in Uwandani Shehia area is similar to other moderate transmission areas in SSA (Bocanegra et al, 2015;Okeke and Ubachukwu, 2014;Robinson et al, 2009). Hence, these variations in performance of the urine reagent strips in low transmission settings will require confirmation of positive results with more sensitive diagnostic tests.…”
Section: Discussionsupporting
confidence: 89%
“…For these reasons, the diagnostic reliability of having trained and experienced personnel to identify the presence of macroscopic blood in the urine has also been assessed, again, comparing the method to urine-egg detection by microscopy (Okeke and Ubachukwu, 2014). Once more it was concluded that, unless used in conjunction with more taxing and costly methods, macrohematuria does not provide adequate sensitivity when compared to egg microscopy, and in using only this method low-, or even moderate-intensity, infections would likely be missed.…”
Section: Macroscopic Changes To Urine As a Means Of Diagnosing Urogenmentioning
confidence: 99%
“…Haematuria is defined as the presence of red blood cells in urine. It can be detected by macroscopic urinalysis, where the presence of blood in urine is seen by naked eye, or via microscopic urinalysis, where the use of a microscope is needed [6]. Studies have shown that people shedding S. haematobium eggs also commonly have haematuria [1, 711].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical settings, an automatic urinalysis reader is typically used as it eliminates bias due to subjective reading by naked eye and increases the throughput of read-outs (each read only requires one minute to process) [17]. Portable, battery-operated versions of these devices have been introduced which would, in theory, render them usable in more remote areas [6, 18].…”
Section: Introductionmentioning
confidence: 99%